Pengembangan Media Pembelajaran Instruksional (LUDO) Terhadap Karakteristik Siswa - Puji Febriana Islamia; Farradina Latif; Fauziah Anugrah; Elfiandi Rizaldi; Alfiatussyifa Alfiatussyifa (LPPM Politeknik Pratama, 2024)
Education is not just a process of obtaining information but has a role in character formation. Over time, the educational paradigm has undergone very significant changes, one of the most prominent forms of transformation is the use of learning models in the learning process in education today. Each student has unique characteristics that influence the way they learn and interact. Some students may be more responsive to visual learning methods, while others tend to explore the material more through an auditory or kinesthetic approach. Characteristics such as motivation, creativity and independence also influence how students can face learning challenges. In an effort to realize more holistic learning, the development of instructional media appears as a solution to student characteristics, opening the door to more creative and adaptive education. The research method used is development research methods. The development model chosen is learning design development which refers to the Instructional Development Model (MPI) by Suparman (2014: 131). This research uses the Instructional Development Model (MPI) with the media we use consisting of 2 media, the first LUDO and KOMA. The implementation of the media starts from the development, development, broadcast and revision stages. Reading processional material is a systematic thinking process to help students learn from existing learning materials. With the LUDO and KOMA learning media, students can easily understand the material and are enthusiastic about learning because they can understand the learning. These learning methods and media will help the process of delivering open material to students. Harmony between learning methods and media and the learning material itself will produce meaningful learning for students.